Advaita Vedanta dalam Teks Śvetāśvatara Upaniṣad - Mery Ambarnuari; Hari Harsananda (Sanjiwani: Jurnal Filsafat, 2021)
The emergence of sampradaya polemics and frictions that often arise in understanding aspects of divinity bring back our memories of the divine philosophical system in Hinduism, namely: Dwaita, Visisthadvaita and Advaita. One of the texts containing the teachings of Advaita Vedanta is the Śvetāśvatara Upaniṣad. The Advaita philosophy in the mantras contained in the Śvetāśvatara Upaniṣad explicitly shows that everything that exists in this world is God (Brahman). The concept of Brahman in Advaita philosophy asserts that Brahman is not an object of worship so that the concept of devotional service between the worshiped and the worshiped is not found in the Advaita Vedanta teachings. In the concept of Advaita Vedanta, God (Brahman) has the same essence as atman, so for humans in order to find their identity which is the same as Brahman, they should do contemplation through the teachings of Yoga. Yoga plays a role as a method in an effort to purify the material elements which are mostly composed of maya elements. Purifying the virtual element which includes humans is tantamount to increasing the level of spiritual awareness of the atman so that it can return to a pure spirit entity without the virtual element or return to the paramatman entity (Moksa). Such is the doctrine of Advaita Vedanta contained in the Svetasvatara Upanisad.